PENGARUH INTERNSHIP MAHASISWA, TRANSFER PENGETAHUAN, DAN KOMPETENSI DIGITAL TERHADAP KINERJA LAYANAN INFORMASI PEMERINTAH - Liah Lestari; I Dewa Ketut Kerta Widana (ITB Swadharma, 2026)
This study aims to examine and measure the influence of the student internship program (student interns), the knowledge transfer process, and digital competency on the performance of government information service units. The research used a quantitative, explanatory approach. Data were obtained through questionnaires distributed to employees and interns at government information service units, supplemented by brief interviews. Statistical analysis used multiple linear regression to determine each variable's contribution. The following results were obtained: (1) the student internship program has a positive impact on service quality through additional human resources, adaptive capabilities, and digital skills relevant to the information service unit; (2) knowledge transfer plays a role in strengthening the learning process and maintaining service standards at government information service units; (3) digital competency is the variable that most influences the performance of information service units, as evidenced by the increased effectiveness of technology use, the accuracy of information delivered, and the speed of response to the public. The collaboration among the internship program, knowledge-sharing mechanisms, and improvements in digital competency is a key factor in strengthening the performance of government information services in the digital era.Penelitian ini bertujuan untuk menguji dan mengukur pengaruh program internship mahasiswa (mahasiswa magang), proses transfer pengetahuan, dan kompetensi digital terhadap kinerja unit layanan informasi pemerintah. Metode penelitian menggunakan metode kuantitatif dengan pendekatan eksplanatori. Data diperoleh melalui penyebaran kuesioner kepada pegawai dan peserta magang (internship) di unit layanan informasi pemerintah, dilengkapi wawancara singkat. Analisis statistik menggunakan regresi linier berganda untuk mengetahui kontribusi masing-masing variabel. Hasil penelitian yang diperoleh : (1) program mahasiswa magang memberikan dampak positif terhadap kualitas layanan melalui tambahan sumber daya manusia, kemampuan adaptif, serta keterampilan digital yang relevan dengan unit layanan informasi; (2) transfer pengetahuan berperan memperkuat proses pembelajaran serta menjaga standar pelayanan unit layanan informasi pemerintah; (3) kompetensi digital merupakan variabel yang paling berpengaruh terhadap kinerja unit layanan informasi, terlihat dari meningkatnya efektivitas penggunaan teknologi, ketepatan informasi yang disampaikan, serta kecepatan respon kepada publik. Sinergi antara program magang, mekanisme berbagi pengetahuan, dan peningkatan kompetensi digital merupakan faktor kunci dalam memperkuat kinerja layanan informasi pemerintah pada era digital